Potential Beneficial Effects of Hydroxyapatite Nanoparticles on Caries Lesions In Vitro-A Review of the Literature - Eisha Imran; Paul R. Cooper; Jithendra Ratnayake; Manikandan Ekambaram; May Lei Mei (MDPI AG, 2023)
Dental caries is one of the most common human diseases which can occur in both primary and permanent dentitions throughout the life of an individual. Hydroxyapatite is the major inorganic component of human teeth, consequently, nanosized hydroxyapatite (nHAP) has recently attracted researchers' attention due to its unique properties and potential for caries management. This article provides a contemporary review of the potential beneficial effects of nHAP on caries lesions demonstrated in in vitro studies. Data showed that nHAP has potential to promote mineralization in initial caries, by being incorporated into the porous tooth structure, which resulted from the caries process, and subsequently increased mineral content and hardness. Notably, it is the particle size of nHAP which plays an important role in the mineralization process. Antimicrobial effects of nHAP can also be achieved by metal substitution in nHAP. Dual action property (mineralizing and antimicrobial) and enhanced chemical stability and bioactivity of nHAP can potentially be obtained using metal-substituted fluorhydroxyapatite nanoparticles. This provides a promising synergistic strategy which should be explored in further clinical research to enable the development of dental therapeutics for use in the treatment and management of caries.